Atomic Broadcast and Quorum-based Replication in Asynchronous Crash-Recovery Distributed Systems - Rodrigues, Luís (2009)
This paper describes a solution to the Atomic Broadcast problem in asynchronous distributed systems in which processes can crash and recover. Our solution is based on a transformation of any Consensus algorithm into an Atomic Broadcast algorithm. Thus, our work can benefit from recent results in the study of the Consensus problem in the crash-recovery model. The paper also shows how to extend the Atomic Broadcast primitive to support the implementation of Quorum-based replica management in crash-recovery systems. The proposed technique makes a bridge between established results on Weighted Voting and recent results on the Consensus problem.